FAKTOR – FAKTOR YANG MEMPENGARUHI KESIAPAN KERJA SISWA SMK JURUSAN KOMPETENSI KEAHLIAN AKUNTANSI KEUANGAN LEMBAGA - Maria Ayu Trivena; Supri Wahyudi Utomo; Farida Styaningrum (Jurnal Muara Pendidikan, 2025)
The open unemployment rate among vocational high school graduates remains a serious problem, even though vocational schools are designed to produce work-ready graduates. This phenomenon indicates a gap between the needs of the workforce and the competencies of graduates.This study aims to identify and analyze factors that influence the work readiness of Grade XI students majoring in Financial Accounting at SMKN 1 Gemarang. This study used a quantitative approach with an ex post facto type, involving 49 students as respondents, and data were collected through a Likert-scale questionnaire. The analysis was carried out through instrument testing (validity and reliability), classical assumption tests (normality, linearity, multicollinearity, and heteroscedasticity), and inferential statistical tests (partial t-test and coefficient of determination). The results showed that work readiness was significantly influenced by Field Work Practice. Meanwhile, family environment, accounting competency, self-efficacy, and motivation did not significantly influence work readiness. This finding emphasizes the importance of optimizing the Field Work Practice program as a means of improving students' readiness to enter the workforce..